Phytochemical Analyses, Glucose Stimulatory Effects and Cytotoxicity of Cassia abbreviata and Helinus integrifolius Leaf Extracts in in vitro Cell Cultures - Olaokun, O.O.; Ntini, V.P. (Asian Journal of Chemistry, 2023)
Numerous phytochemical constituents are found in plants and have been used either as single entities or extracts to treat various ailments. This study investigated the extracts of Cassia abbreviata and Helinus integrifolius in vitro for phytochemicals and its effect on glucose utilization of C2C12 muscle and H-4-II-E liver cells and for cytotoxicity against raw 264.7 cells using the real-time xCelligence system method. The ethyl acetate and acetone extracts of phenolic rich C. abbreviata stimulated greater C2C12 muscle cells glucose utilization at concentrations of 0.065 mg/mL and 0.125 mg/mL and acetone extract of C. abbreviata enhanced a concentration dependent H-4-II-E cells glucose utilization. For cytotoxicity, all extracts in concentration dependent manner decreased the viability of the raw 264.7 cells in real time assay with concentrations of 0.05 mg/mL the least cytotoxic. The extracts of C. abbreviata in in vitro assay demonstrated glucose stimulatory potential but further investigation of the cytotoxicity is required.